Baumol versus Engel: Accounting for 100 years (1885-1985) of Structural Transformation in Japan - Kyoji Fukao; Saumik Paul (Institute of Labor Economics (IZA), 2019)
This paper examines the drivers of the long-run structural transformation in Japan. We use a dynamic input-output framework that decomposes the reallocation of the total output across sectors into two components: the Engel effect (demand side) and the Baumol effect (supply side). To perform this task, we employ 13 seven-sector input-output tables spanning 100 years (1885 to 1985). The results show that the Engel effect was the key explanatory factor in more than 60% of the sector-period cases in the pre-WWII period, while the Baumol effect drove structural transformation in more than 75% of such cases in the post-WWII period. Detailed decomposition results suggest that in most of the sectors (agriculture, commerce and services, food, textiles and transport, communication and utilities), changes in private consumption were the dominant force behind the demand-side explanations. The Engel effect was found to be the strongest in the commerce and services sector, which contributed to the rapid growth of GDP in Japan throughout the 20th century.
Keywords: O40; O10; 330; long-run structural transformation; the Engel effect; Baumol's cost disease effect; sectoral productivity growth